Isotopic signatures suggest important contributions from recycled gasoline, road dust and non-exhaust traffic sources for copper, zinc and lead in PM10 in London, United Kingdom. (September 2017) - Dong, Shuofei; Ochoa Gonzalez, Raquel; Harrison, Roy M.; Green, David; North, Robin; Fowler, Geoff; Weiss, Dominik
Abstract: The aim of this study was to improve our understanding of what controls the isotope composition of Cu, Zn and Pb in particulate matter (PM) in the urban environment and to develop these isotope systems as possible source tracers. To this end, isotope ratios (Cu, Zn and Pb) and trace element concentrations (Fe, Al, Cu, Zn, Sb, Ba, Pb, Cr, Ni and V) were determined in PM10 collected at two road sites with contrasting traffic densities in central London, UK, during two weeks in summer 2010, and in potential sources, including non-combustion traffic emissions (tires and brakes), road furniture (road paint, manhole cover and road tarmac surface) and road dust. Iron, Ba and Sb were used as proxies for emissions derived from brake pads, and Ni, and V for emissions derived from fossil fuel oil. The isotopic composition of Pb (expressed using 206 Pb/ 207 Pb) ranged between 1.1137 and 1.1364. The isotope ratios of Cu and Zn expressed as δ 65 CuNIST976 and δ 66 ZnLyon ranged between −0.01‰ and +0.51‰ and between −0.21‰ and +0.33‰, respectively. We did not find significant differences in the isotope signatures in PM10 over the two weeks sampling period and between the two sites, suggesting similar sources for each metal at both sites despite their different traffic densities. The stable isotope composition of Pb suggests significant contribution from road dust resuspension and from recycled leaded gasoline. The Cu and Zn isotope signatures of tires, brakes and road dust overlap with those of PM10 . The correlation between the enrichments of Sb, Cu, Ba and Fe in PM10 support the previously established hypothesis that Cu isotope ratios are controlled by non-exhaust traffic emission sources in urban environments (Ochoa Gonzalez et al., 2016). Analysis of the Zn isotope signatures in PM10 and possible sources at the two sites suggests significant contribution from tire wear. However, temporary additional sources, likely high temperature industrial emissions, need to be invoked to explain the isotopically light Zn found in 3 out of 18 samples of PM10 . Highlights: Copper, Zn and Pb isotope ratios of PM10 at two sites with different traffic densities in London were determined. Stable isotopic compositions of Cu, Zn and Pb suggest similar sources for these trace metals at both sites. Anthropogenic sources including recycled gasoline and road dust remain important for lead. Non-exhaust emissions are the major source of Cu in PM10 . Re-suspended road dust and non-exhaust traffic sources dominate the sources of Zn.